2018
DOI: 10.1002/chem.201803410
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Dimeric Base‐Stabilized Cobaltosilylene Complex for Catalytic C−H Bond Functionalization and C−C Bond Formation

Abstract: The synthesis of a dimeric base-stabilized cobaltosilylene complex and its catalytic reactions are described. Treatment of the amidinato silicon(I) dimer [LSi:] (1; L=PhC(NtBu) ) with CoBr in toluene for 10 days afforded the dimeric amidinato cobaltosilylene [(LSi)μ-{CoBr(LSiBr)}] (2), which is speculated to proceed via "LSiCoBr" and "LSiBr" intermediates in the reaction. Compound 2 is paramagnetic, with an effective magnetic moment of 2.8 μB. Its electronic structure was elucidated by single-crystal X-ray cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…[47][48][49] The structural parameters of the amidinate ligand do not deviate from the starting material. In general, four-membered [M-Si(II)] 2 -rings (M = transition metal) are rare [50][51][52][53] and only a few examples are known for Ni. [54][55][56][57][58] However, the bonding situation and the nature of the silylene is different in those complexes (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49] The structural parameters of the amidinate ligand do not deviate from the starting material. In general, four-membered [M-Si(II)] 2 -rings (M = transition metal) are rare [50][51][52][53] and only a few examples are known for Ni. [54][55][56][57][58] However, the bonding situation and the nature of the silylene is different in those complexes (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, N-heterocyclic silylene (NHSi) as a heavier analogue of N-heterocyclic carbene (NHC) has attracted extensive attention. 1,2 With the development of studies of transition metal NHSi complexes, it is found that NHSi complexes exhibit excellent catalytic activities in many catalytic reactions, such as hydrosilylation of aldehydes and ketones, 3,4 hydrosilylation of olefins, 5,6 reduction of amides, 7 boration, 8 C–C coupling, 9 and nitrogen fixation. 10,11 In some catalytic systems, the introduction of NHSi ligands even enabled the catalyst to perform better than related NHC or phosphine complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, So et al reported the formation of the bimetallic disilylene Rh and Ir complexes II and III (Scheme a) . Also, the dinuclear iron­(II)­bromide complex IV is formed cleanly, but the Si–Si bond is cleaved by cobalt­(II)­bromide to form dinuclear cobalt­(bromosilylene)­(silyl) complex V . To the best of our knowledge, no mononuclear metal adducts of ligand I are reported to date.…”
Section: Introductionmentioning
confidence: 99%